A geography of the Hutterites in North America - Evans, S. M. 1937-2019 (University of Nebraska Press, 2021)
"A Geography of the Hutterites in the New World, 1874-2019 maps and analyzes the German-speaking religious brotherhood and focuses on the community's pattern of population growth, additions to the cultural landscape of the northern plains, and contributions to both the agricultural and light manufacturing economies of their home states and provinces"--